(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
There were fewer obstacles to marine shipping in the past than there are now. The marine sector, like all others, must evolve to meet the requirements of the contemporary world and operate in a sustainable manner. Constant advances in technology and growing concern for the environment drive today’s shipping industry. Therefore, protecting the marine environment through the implementation of innovative solutions is one of the primary challenges of maritime transport. However, it is difficult to simultaneously improve the environment and the economy. That’s why it’s crucial to work towards a marine transport future where everyone benefits from its growth. This article presents an overview of the important elements to consider in developing sustainable shipping, including available and prospective technology solutions, logistical operations, and regulatory regulations employed in lowering shipping gas emissions. Additionally, novel strategies for complying with the ever-tightening environmental regulations are discussed.